Always Making Progress The Fundamentals of Continuous Improvement for the Process Industry. - Madden, Ian. (Milton : Productivity Press, 2022)
This book guides process-industry professionals from the implementation of the basic foundations of Continuous Improvement (CI) through to an organization where CI is a way of life and a defining feature of the culture of the organization. The readers of this book are seeking solutions to such pressing issues as: Eliminating accidents and near misses. Reducing customer complaints. Improving customer delivery performance. Elimination of accidents and near misses. Reducing customer complaints. Improving customer delivery performance. Introducing new products. Improving staff productivity. Removing costs to meet the budget. Dealing with absence and poor morale. Improving staff retention. This book provides them with guidance on how to address issues in these areas in a way that enables improvements to be realized quickly but not at the expense of a long-term goal of a sustainable Continuous Improvement culture. In addition, this book presents the implementation of CI as a cyclical journey with no endpoint. The stages are ordered in a sequence that enables the reader to get started in their area of the company and build up the elements without the need for an overall organizational strategy at the beginning. Continuous Improvement is a vast subject with many takes on principles, approaches, and tools. This book is about how all the fundamentals of these areas fit together and, as such, covers only some of them. However, within the bibliography, I have signposted the books that have guided me during my career and which go into the principles, approaches, and tools further.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Total Quality Management; BUSINESS & ECONOMICS / Quality Control; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; Continuous improvement process; Production management; Industrial productivity